Investigating the effectiveness of structured mindfulness sessions in mitigating burnout among final-year dental students: A mixed-methods analysis - Aliya Islam; Javeria Rehman; Sumbul Mujeeb; Rubab Javed; Unaiza Hashmi; Tazeen Saeed Ali (PLoS ONE, 2026)
Background The transition from dental student to practicing dentist is often accompanied by high level of stress and risk of burnout. This shift from academic to professional roles can overwhelm students and compromise their well-being. Addressing burnout early is essential to maintain academic performance, resilience, and quality patient care. Mindfulness interventions have shown increasing empirical support in reducing stress and burnout. This mixed-methods study evaluated the effectiveness of mindfulness-based life skill-building sessions in alleviating burnout among final-year dental students at Baqai Dental College, Karachi, Pakistan. Method A sequential mixed-method study was conducted at Baqai Dental College in Karachi, Pakistan, involving sixty-nine final-year dental students. The intervention comprised two mindfulness sessions. Participants completed pre- and post-intervention questionnaires that included demographic information and the Copenhagen Burnout Inventory–Student Survey (CBI-SS), a validated 25-item tool assessing burnout across four domains: personal, study-related, colleague-related, and teacher-related. Post-intervention questionnaires were completed immediately after the sessions. Qualitative data were obtained through focus group discussions with stakeholders to explore perceptions of burnout and assess the relevance and feasibility of mindfulness sessions. Quantitative data were analyzed using paired t-tests, while qualitative data were examined through content analysis and triangulated with literature and documentation. Result Diverse emotions and experiences were revealed through qualitative analysis, underscoring the substantial influence of exhaustion on personal, academic, and professional domains. Furthermore, the mean exhaustion scores were significantly different between the pre- and post-intervention periods, with a p-value of 0.001. Students conveyed satisfaction and a desire for more meaningful sessions that bolster life-building skills. Conclusion The study findings demonstrate a decrease in burnout rates following the intervention, indicating the necessity for interventions to mitigate academic stress. Qualitative findings underscore the significance of a student support centre and self-care initiatives.